Successful percutaneous mechanical thrombectomy treatment for a patient with chronic deep vein thrombosis: a case report - Maranatha, Maranatha; Yasa, Ketut Putu (Journal of Indonesia Vascular Access, 2025)
Background: This case report details the management of atypical chronic deep vein thrombosis (DVT) in a 24-year-old male. The treatment of DVT is complex and case-dependent; however, most individuals are managed with oral anticoagulation therapy, while complex cases can be treated with advanced interventions. Only a few publications discuss about endovascular procedure of chronic DVT.  This report discusses a singular case of an atypical or complex DVT undergoing a thrombectomy using an Indigo Penumbra system. Case illustration: A 24-year-old male was admitted to the hospital with bilateral leg swollen for 8 years ago. His history was unremarkable, and he was diagnosed with bilateral lower extremities deep vein thrombosis and was routinely administered anticoagulants. Laboratory results showed a significant increase in d-dimer levels. Venography confirmed bilateral deep vein thrombosis in the femoral vein system. He then underwent percutaneous mechanical thrombectomy with the Indigo Penumbra system. Small fragments of white thrombus were collected from the system container. He was discharged 1 day post-operatively and scheduled for further workup. Conclusion: This case report elaborates on a patient with an atypical chronic white thrombus DVT who underwent a thrombectomy after imaging showed extensive thrombotic disease in the right lower extremity. Despite the few publications, percutaneous mechanical thrombectomy using the Indigo Penumbra System showed promising results in chronic DVT.